Literasi Digital Berbasis Sosialisasi Bicara Baik dan Bijak Bermedia Sosial pada Kelompok Ibu Rumah Tangga Kel. Sungai Sibam Kota Pekanbaru - Ulmi Marsya; Arina Himatul Husna; Nazhifah; Johan Faladhin; Desy Mairita; M.Tazri (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
High intensity of social media usage in indonesia provides online interaction between people all around the world anytime. Social Media users can having some online interactions with which public figures they want to as long as they also use the social media. communication activity such as sending messages, likes, comment can be done. But, Indonesian netizen are often do some aggressive or rude act in online media. There are some factors like the anonymous and tons of comments all over the world makes them feel safe to comment as they please. They can do any hate speech or something offensive easily to other people that they even never know each other before. Especially for women, social media is whare any gender violances such as sexual harassment, gender justifications, or anything else can do even in online public spaces. According to those problems above, digital literacy is really important to women to makes they know how to use social media safely and in positive ways from how to access, how to understanding the message, and how to select good informations.